Current Diagnosis and Classification of Hepatic Encephalopathy - Amodio, Piero (J Clin Exp Hepatol, 2018)
Hepatic encephalopathy is a brain dysfunction caused by liver insufficiency and/or portal-systemic shunt; it manifests as a wide spectrum of neurological or psychiatric abnormalities ranging from subclinical alterations to coma. It should be differentiated from other neurological/psychiatric disorders that can occur in patients with liver disease. Its classification needs to take into account the underlying condition, severity, course, precipitating factors, and—possibly—sensitivity to ammonia-lowering agents.